1987
DOI: 10.1172/jci112925
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates volume absorption in the rabbit proximal convoluted tubule.

Abstract: The present in vitro microperfusion study examined whether insulin affects volume absorption (J.) in the proximal convoluted tubule (PCT). PCT were perfused with an ultrafiltrate-like solution and were bathed in a serum-like albumin solution. Addition of a physiologic concentration of 10-10 M insulin to the bathing solution resulted in a stimulation of J. and a more negative transepithelial potential difference (PD). There was a progressive stimulation of the lumen negative PD and J, with higher insulin conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
128
2
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(136 citation statements)
references
References 25 publications
1
128
2
3
Order By: Relevance
“…Epidemiological studies indicate that insulin resistance and arterial hypertension are interrelated [35,36]. It has been suggested that the prohypertensive action of insulin could be due to increased sodium reabsorption by acting on distinct segments of the renal tubule [37][38][39]. A feedback mechanism limits insulininduced sodium retention when extracellular fluid volume is expanded [40], which is impaired in rats with hypertension associated with insulin resistance [41].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicate that insulin resistance and arterial hypertension are interrelated [35,36]. It has been suggested that the prohypertensive action of insulin could be due to increased sodium reabsorption by acting on distinct segments of the renal tubule [37][38][39]. A feedback mechanism limits insulininduced sodium retention when extracellular fluid volume is expanded [40], which is impaired in rats with hypertension associated with insulin resistance [41].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, insulin has an acute antinatriuretic effect [20], even in obese persons resistant to other metabolic effects of the hormone [21]. Although insulin is thought primarily to affect distal tubular sodium re-absorption [21,22,23,24], there is evidence of a direct insulin action on proximal tubular sodium re-absorption [25,26]; moreover, insulin receptors have been found in the proximal tubule of different species [27,28,29]. Finally, insulin increases the expression and the activity of sodium-hydrogen exchange isoform 3, which mediates more than 60% of the sodium re-absorption at the proximal tubule [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia in vitro favours antinatriuresis due to enhanced glucose-sodium co-transport in the convoluted proximal tubule [25]. In vivo proximal sodium re-absorption is stimulated by hyperglycaemia in rats [36], and is higher in patients with diabetes [37].…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible mechanisms by which insulin could increase blood pressure. Insulin increases sodium and water reabsorption in the proximal tubules of the kidney (22). Even with increased peripheral insulin resistance, as in hypertension (23) and obesity (24), the effect of insulin in the kidney seems to be preserved.…”
Section: Discussionmentioning
confidence: 99%